The role of the TrkB-T1 receptor in the neurotrophin-4/5 antagonism of brain-derived neurotrophic factor on corticostriatal synaptic transmission - Hernández-Echeagaray, Elizabeth (Neural Regen Res, 2020)
This manuscript reviews the function and fundamental characteristics of the neurotrophins and their receptors to introduce the reader to the differential effects exhibited by the neurotrophins; brain-derived neurotrophic factor and neurotrophin 4/5 when acted together after sequential presentation. The neurotrophin 4/5 exhibits an inhibitory action on the modulatory effect of brain-derived neurotrophic factor in corticostriatal synapses when they are administered sequentially (brain-derived neurotrophic factor to neurotrophin 4/5). This inhibitory effect has not been previously documented and is relevant for these neurotrophins as both of them stimulate the TrkB receptor. The additive effect of these neurotrophins is also discussed and occurs when neurotrophin 4/5 exposure is followed by brain-derived neurotrophic factor in a mouse model of striatal degeneration. Occlusive and additive effects of both neurotrophins are accompanied by changes in the expression of the TrkB receptor isoforms, specifically TrkB-T1 and TrkB-FL, as well as differences in phosphorylation levels of the TrkB receptor. The results of the experiments described raise several questions to inquire about the role that TrkB-T1 receptor plays in striatal physiology, as well as the functional relevance of the interaction of brain-derived neurotrophic factor and neurotrophin 4/5 in the brain and more specifically at the striatal circuits in normal as well as pathological conditions.